Evaluating societal preferences for human papillomavirus vaccine and cervical smear test screening programme. Issue 1 (18th October 2010) - Oteng, Bridgette; Marra, Fawziah; Lynd, Larry D; Ogilvie, Gina; Patrick, David; Marra, Carlo A
Abstract : Background: Cervical cancer and genital warts are diseases associated with human papillomavirus (HPV) infection. Cervical smear testing is used as a cervical cancer screening tool in most countries worldwide. The newly introduced vaccines that prevent HPV infections are the quadrivalent vaccine (Gardasil), which prevents genital warts and cervical cancer, and the bivalent vaccine (Cervarix), which prevents cervical cancer only. Public preferences for HPV vaccines and smear test screening were determined using a discrete choice experiment. Methods: Participants from across Canada completed a choice-based questionnaire to measure preferences from which willingness to pay (WTP) was calculated for the following: (1) lifetime risk of cervical cancer and genital warts, (2) frequency of smear testing, (3) need for vaccine booster, (4) target group to vaccinate, (5) frequency of side effects and (6) cost of the vaccine (from 2008). A mixed effect logistic model was used to analyse the data. Results: Of the 1157 participants, the mean age was 44 years (SD 15) and 49% were women. Respondents preferred a vaccine that gave lifelong immunity, a vaccination programme that targeted boys and girls and a vaccine that gave protection from genital warts and cervical cancer. Respondents were averse to yearly smear testing. On average, respondents were willing to pay $C53 and $C22 to avoid a 1% increase in the risk of cervical cancer and genital warts, respectively. Conclusions: Society agrees with the introduction of the HPV vaccination programme, but would prefer a programme that targets boys and girls with the quadrivalent vaccine.